Reactividad álcali – sílice, de las combinaciones cementantes con los agregados pétreos de las minas Cerro Negro y Río Chambo - Villagómez Avilés, Cristhian Javier (2019)
The whole world has been concerned about the degradation of concrete, it has a lot of causes and consequences, one of the most important is the one that it originated by the expansive reactions of concrete, where the Alkalis-silica reaction, which acronyms are in English (ASR), is one of the most harmful, it’s because of the great amount of aggregates potentially activate this reaction, the same that causes the expantion of the concrete, this occurs when the chemical reaction of the alkali and the cement meets the silica from the aggregates. In the following work, the properties of the aggregates were studied from the main quarry companies in Riobamba, and their possibly ASR in concrete In this investigation two studies were done in order to determinate the reactivity alkalis-silica of the materials, the fluorescence of x rays in the two types of cement ( IP, GU) in order to know the elements alkaline in each one, and, the experiment of the mortar bar to measure the expantion of the bars and determinate its possible reactivity The results of this investigation, indicate that one of the cement materials, tents to be more susceptible to this reaction, because the expantion is too great, and it’s not acceptable in Ecuadorians and Americans standards